MANAJEMEN KEUANGAN UMKM (USAHA MIKRO KECIL DAN MENENGAH) DI KOTA MEDAN - faisal akbar faisal (Fakultas Ekonomi Prodi Akuntansi, 2022)
Abstract The ability and knowledge of small businesses to management science is very lacking, especially in the financial sector. Although most of these entrepreneurs have had formal education, not all of them have a financial management background. The purpose of this study was to find out ways to manage finances well by MSME actors (Micro, Small and Medium Enterprises). This study uses a descriptive and qualitative approach by means of documentation. The results obtained are that the first is mastery of financial statements by means of financial management by separating business finance and personal finance, determining the amount of financial percentage, carrying out financial records (bookkeeping), reducing the risk of accounts payable, and controlling the smooth flow of business cash, controlling the smooth flow of cash. business. And the financial reports required by MSMEs are certainly different from the financial reports for large companies. Seeing the complexity and smaller size of the business, the financial statements that need to be prepared become simpler both financial literacy in the form of financial skills as a technique for making decisions in financial management behavior and financial tools as a means used in making financial management decisions.